Domestication of farmed fish via the attenuation of stress responses mediated by the hypothalamus–pituitary–inter-renal endocrine axis - Lu, Yao; Shi, Chuang; Jin, Xia; He, Jiangyan; Yin, Zhan (Frontiers in Endocrinology, 2022)
Human-directed domestication of terrestrial animals traditionally requires thousands of years for breeding. The most prominent behavioral features of domesticated animals include reduced aggression and enhanced tameness relative to their wild forebears, and such behaviors improve the social tolerance of domestic animals toward both humans and crowds of their own species. These behavioral responses are primarily mediated by the hypothalamic–pituitary–adrenal (inter-renal in fish) (HPA/I) endocrine axis, which is involved in the rapid conversion of neuronal-derived perceptual information into hormonal signals. Over recent decades, growing evidence implicating the attenuation of the HPA/I axis during the domestication of animals have been identified through comprehensive genomic analyses of the paleogenomic datasets of wild progenitors and their domestic congeners. Compared with that of terrestrial animals, domestication of most farmed fish species remains at early stages. The present review focuses on the application of HPI signaling attenuation to accelerate the domestication and genetic breeding of farmed fish. We anticipate that deeper understanding of HPI signaling and its implementation in the domestication of farmed fish will benefit genetic breeding to meet the global demands of the aquaculture industry.